Exploring the need for health education specialists in local health departments in Wisconsin - Nutt, Tessa (My University, 2018)
The utilization of health education specialists in local health departments varies immensely across Wisconsin. Health education specialists’ roles and responsibilities within the local health department setting are not clearly defined or delineated. There is much ambiguity surrounding health education specialists, especially in the eyes of employers. The purpose of this project was to explore how local health departments in Wisconsin use, or fail to use, health education specialists. The La Crosse County Health Department assisted in developing a survey about the roles and responsibilities of health education specialists in local health departments and the workforce structure of the health departments. The survey was completed by 92 respondents to include health officers and health education specialists around Wisconsin. The results revealed a need for employer education about health educators and their educational backgrounds as well as credentialing opportunities for health educators. Results from the survey can be utilized by employers to create rationales for hiring health education specialists, restructuring their workforces, and expanding their knowledge of the skill sets of health education specialists.
Keywords: Health education; Health education teachers; Public health